LEMBAGA PENYELENGGARAAN KESEJAHTERAAN SOSIAL ANAK YANG BERHADAPAN DENGAN HUKUM DI KABUPATEN KUBU RAYA - Puji, Eri Putri Maharani Apriliano; Purnomo, Yudi; Affrilyno, Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Children in Conflict with the Law (CICL) are minors involved in legal processes due to violations of law. In Kubu Raya Regency, the increasing number of CICL has not been supported by adequate rehabilitation and development facilities. Therefore, this study focuses on the architectural design of a Social Welfare Organizing Institution (LPKS) that provides a safe, comfortable, and supportive environment for rehabilitation and social reintegration. The main objective of this design project is to develop a facility that meets the functional, psychological, and social needs of CICL through the application of principles of safety, comfort, and educational value. The design method includes user needs identification, space standard analysis based on LPKS regulations, and the application of contextual design concepts emphasizing environmental sustainability and local wisdom. The result is an integrated spatial concept consisting of residential, training, counseling, and recreational zones, designed with secure circulation and effective visual supervision. This design aims to serve as a model for humane, adaptive, and socially restorative facilities for children in conflict with the law.